Fostering Engaged Pedagogical Innovation for Meaningful Learning: A Literature Review (Pragyaratna प्रज्ञारत्न, 2023)
Teaching and learning of mathematics become unpractical and meaningless while students are treated as passive beings and teachers are treated as the knowledge transformers. In this paper, I have explored some key ideas regarding meaningful pedagogical approaches in teaching mathematics based on the in-depth study and critical analysis of the efforts of various authors together with my reflective ideas. Students’ performance in mathematics appears deficient, largely due to the limited implementation of pedagogical approaches that cater to their interests and establish meaningful connections to their daily lives in the classroom. Furthermore, instead of applying engaged pedagogical approaches; disengaged and decontextualized pedagogical approaches seem in daily practice. As the result, mathematics is not becoming as the subject of the interest of most of the student. This paper is intended to explore the different techniques of teaching and learning of mathematics effectively to foster active involvement of the learners. Moreover, through this study, I have critically analysed and reflected the contributions of many authors regarding enabling pedagogical approaches demonstrated by them to reach in final conclusion. From my critical self-reflection with reference to many authors, I have concluded that there are some pedagogies that inspire students to engage in learning mathematics.